The identity of Onosma liui (Boraginaceae) from Sichuan, China - He, Yi; Liu, Danhui; Wu, Kai; Liu, Quan-Ru (Phytotaxa, 2019)
Examination of specimens, literature and critical field survey has shown that Onosma liui is conspecific with O. maaikangensis, an endemic species distributed in Western Sichuan and Eastern Xizang, China. Therefore, we place the former in synonymy with the latter.